Lexical Meaning in Truth-Conditional Semantics (Diametros, 2014)
The paper offers a critical review of the role played by lexical meaning in the earlier stages of philosophical semantics and truth-conditional semantics. I shall address, both historically and theoretically, the relative neglect of lexical semantics within these fields, and argue that the approach to word meaning fostered in extensional frameworks is overall inconsistent with the customary assumption that truth-theoretic semantics can be considered a semantic theory proprio sensu.
Keywords: word meaning; lexicon; reference; theories of meaning; semantics